2013
DOI: 10.1371/journal.ppat.1003100
|View full text |Cite
|
Sign up to set email alerts
|

Binding of HIV-1 gp120 to DC-SIGN Promotes ASK-1-Dependent Activation-Induced Apoptosis of Human Dendritic Cells

Abstract: During disease progression to AIDS, HIV-1 infected individuals become increasingly immunosuppressed and susceptible to opportunistic infections. It has also been demonstrated that multiple subsets of dendritic cells (DC), including DC-SIGN(+) cells, become significantly depleted in the blood and lymphoid tissues of AIDS patients, which may contribute to the failure in initiating effective host immune responses. The mechanism for DC depletion, however, is unclear. It is also known that vast quantities of viral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 65 publications
0
16
0
Order By: Relevance
“…This finding partially explains the DC depletion in chronically infected HIV-1 patients (36). On the other hand, HIV-1 replication in DCs requires DC-SIGN signaling triggered by gp120 and binding of gp120 to DC-SIGN-induced kinase Raf1-dependent phosphorylation of the NF-B subunit p65, which could recruit the transcription elongation factor pTEF-b, demonstrating that DC-SIGN signaling triggered by gp120 is essential for HIV-1 transcription elongation (37).…”
Section: Journal Of Biological Chemistry 22983mentioning
confidence: 88%
“…This finding partially explains the DC depletion in chronically infected HIV-1 patients (36). On the other hand, HIV-1 replication in DCs requires DC-SIGN signaling triggered by gp120 and binding of gp120 to DC-SIGN-induced kinase Raf1-dependent phosphorylation of the NF-B subunit p65, which could recruit the transcription elongation factor pTEF-b, demonstrating that DC-SIGN signaling triggered by gp120 is essential for HIV-1 transcription elongation (37).…”
Section: Journal Of Biological Chemistry 22983mentioning
confidence: 88%
“…So far, to the best of our knowledge, HIV-1 has not been shown to activate DCs, although a previous study suggested that recognition of HIV-1 viral ssRNA by TLR7/8 on plasmacytoid DCs and monocytes may partially contribute to immune activation seen in HIV-infected individuals (43). Other studies have shown that binding of gp120 by DC-specific ICAM-3-grabbing nonintegrin can lead to suppression of IFN-a and apoptosis signal-regulating kinase 1-dependent cell death (46,47). A recent report by Manel and colleagues (48) found that monocyte-derived DCs were unable to respond to HIV-1 in the absence of a productive infection, but when replication could be artificially induced, type I IFN responses were produced.…”
Section: Discussionmentioning
confidence: 99%
“…During later stages of HIV infection, binding of membrane-bound or soluble gp120 with CD4 leads to the apoptosis of HIV-infected and uninfected bystander CD4 + T-cells (Li & Pauza, 2013). In addition, soluble gp120 has been reported to induce apoptosis in a variety of cells such as CD8 + T-cells, neurons, human vascular endothelial cells, cardiomyocytes, oral keratinocytes and renal tubular cells (Chen et al, 2013;Février et al, 2011;Green et al, 2014;Vashistha et al, 2009) through several mechanisms as depicted in Fig. 1(b).…”
Section: Role Of Gp120mentioning
confidence: 99%